If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2g + -4) + -1(3g + -7) = 1 Reorder the terms: 6(-4 + 2g) + -1(3g + -7) = 1 (-4 * 6 + 2g * 6) + -1(3g + -7) = 1 (-24 + 12g) + -1(3g + -7) = 1 Reorder the terms: -24 + 12g + -1(-7 + 3g) = 1 -24 + 12g + (-7 * -1 + 3g * -1) = 1 -24 + 12g + (7 + -3g) = 1 Reorder the terms: -24 + 7 + 12g + -3g = 1 Combine like terms: -24 + 7 = -17 -17 + 12g + -3g = 1 Combine like terms: 12g + -3g = 9g -17 + 9g = 1 Solving -17 + 9g = 1 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 9g = 1 + 17 Combine like terms: -17 + 17 = 0 0 + 9g = 1 + 17 9g = 1 + 17 Combine like terms: 1 + 17 = 18 9g = 18 Divide each side by '9'. g = 2 Simplifying g = 2
| xy^4+x^2y=5x+3y | | 14.6=k/2.5 | | 3n+53=99 | | 3x-1=6x+8 | | 3x-6+2x+3+8x-26=180 | | 3(2x-1)-3=4(-3x+2) | | 9(3-2n)+11n=2 | | 8g+5=-3(g+2) | | y/10+5=-14 | | 2(4x-3)=(6x+4) | | x^2+1800=90x | | 2(3c-6)=5c+8 | | -6-7x+3x=38 | | 5=z+13 | | 8x-3(x-5)=2(x-4)+1 | | -4(3a+5)=-7(2a-5) | | 5(y-3)=3(2y-4) | | x/6+3=6-x/6 | | 3.4y=8.5 | | 6-(x-1)=8 | | 8x^3-y^3= | | 2(3x+2)=(2x-6)+2x | | 5Y-21=2Y | | 5(a-2)=3(4a-5) | | 6p-25=345 | | 3(2y-3)=5(y+1) | | 4(a-7)+4=2a-6 | | 2(x+4)+3=4+7+2x | | -2(3-4x)=7(x+2) | | 0.60x+0.05(12-x)=0.10(-71) | | 33=5v+3 | | 25n=525 |